A system dynamics-based approach to determinants of family business growth - Marques, F.; Ferreira, F.; Zopounidis, C.; Banaitis, A. (Annals of Operations Research, 2022)
Family business growth is crucial not only for the long-term sustainability of this type of firm but also for economic growth as a whole. However, family businesses face internal and external obstacles that hamper their healthy, sustainable growth. Analyses of family business growth are critical to overcoming these barriers. By combining fuzzy cognitive mapping techniques and the system dynamics approach, this study sought to create na analysis model that allows for a more holistic perspective on determinants of family business growth, their cause-and-effect relationships, and thus their long-term behavior. The model developed is a complete, transparent, and realistic tool that enables decision makers to make better and more informed decisions. This study was grounded in the insights provided by a panel of experts in family business, who shared their knowledge and experience over the course of two group sessions. The results of the static and dynamic analyses carried out were validated by the head of department and a board member of the Southern Business Support Center of Portugal’s Institute for the Support of Small and Medium-sized Enterprises and Innovation (IAPMEI). This research’s contributions are also discussed, and suggestions are made for future research.